Judge's Role in Court to Eradicate Corruption According to Law Number 20 in 2001 (Study of Decision 16/PID.SUS.K/2011/PN.MDN) - Rizkan Zulyadi (Budapest International Research and Critics University, 2020)
The main issues in this paper are as follows judge's role in court to eradicate corruption according to law number 20 in 2001 (Study of Decision 16/PID.SUS.K/2011/PN.MDN). This type of research is normative or normative juridical or library legal research which can be interpreted as legal research by examining library materials and secondary materials.The nature of this study is descriptive analytical.This research will be carried out by the researcher is Medan Disrict Court, having his address at Court Road No. 8 Medan Medan City, North Sumatera Province This research will be carried out by researchers starting in December 2018 until completion Data collection techniques are used in writing this essay are through library research techniques and also through the help of electronic media, namely the internet, and the method of data analysis conducted by the author is to use a normative legal approach that examines secondary data. The result shows that the role of the judge in an effort to eradicate corruption cases in the Medan District Court contained in the Decision Study 16/PID.SUS.K/2011/PN.MDN, namely to prosecute the process of corruption cases and impose corruption penalties with imprisonment during 2 (two) years 6 (six) months and a fine of Rp. 50,000,000 (fifty million rupiahs), provided that the fine is not paid, it must be replaced with imprisonment for 2 (two) months.